Using Modified Equipment in Field Hockey Leads to Positive Transfer of Learning Effect - Brocken, Johanna E. A.; van der Kamp, John; Lenior, Matthieu; Savelsbergh, Geert J. P. (Frontiers in Psychology, 2021)
Cross-education is the phenomenon in which repeated practice of a unilateral motor task does not only result in performance improvement of the trained limb, but also in the untrained contralateral limb. The aim of this study was to test whether cross-education or positive transfer of learning is also achieved for tasks in which both limbs contribute in different ways by using modified equipment that switches the limbs’ role. To this end, a reverse field hockey stick was used that requires a mirroring of arm and hand use and dominance (i.e., right hand on top of the hockey stick instead of the left hand). Two groups of young skilled female field hockey players participated in a crossover-design, in which participants received four training sessions with a reverse hockey stick followed by four training sessions with a regular hockey stick, or vice versa. In a pre-test, intermediate test (following the first intervention period), a post-test (after the second intervention period) and a retention test, participants’ performance on a field hockey skill test with a regular hockey stick was measured. The results revealed that training with the reversed hockey stick led to significantly increased improvements compared to training with a regular hockey stick. We conclude that modified equipment can be used to exploit positive transfer of learning by switching the limbs’ roles. The findings are discussed by referring to the symmetry preservation principle in dynamic systems theory and have clear practical relevance for field hockey trainers and players seeking to further improve field hockey skills.